Exploring the Threads of Youth: Stress, BMI, and Menstrual Health in Hang Tuah 2 Senior High School, Sidoarjo - Ronald Pratama Adiwinoto; Qulistan Balqis Ulwani; Lena Wijayaningrum; Stefanus Djoni Husodo; Tasalina Yohana Parameswari Gustam; Hanung Prasetya; I Made Dwi Mertha Adnyana (Utan Kayu Publishing, 2025)
Background: Menstrual cycle disorders are common problems among adolescent girls and are associated with reproductive health issues. Factors such as Body Mass Index (BMI) and stress are believed to influence menstrual irregularities. This study aims to examine the relationship between BMI, stress, and menstrual cycle irregularities as a preventive measure to maintain optimal menstrual health. Method: This observational analytical study utilized a non-probability sampling technique. Data analysis was conducted using Spearman’s Rho Correlation test and Cross Tabulation test at a significance level of 0.05. Results: The analysis showed a significant positive correlation between BMI and menstrual irregularities (p = 0.010, r = 0.258) and between stress and menstrual irregularities (p = 0.001, r = 0.480). Stress exhibited a stronger association with menstrual irregularities than BMI. Conclusion: This study highlights the relationship between BMI and stress with menstrual irregularities in female adolescents at SMA Hang Tuah 2 Sidoarjo. These findings emphasize the need for targeted interventions addressing nutritional and psychological support to improve menstrual health. Monitoring BMI and managing stress are essential strategies to enhance reproductive health in adolescents. Further research is recommended to explore effective interventions to address these factors and improve adolescent well-being.